STUDY ON THE IMPORTANCE OF PHYSICAL EDUCATION AND SPORT CLASSES IN CURRENT SOCIETY - INVESTIGATIVE APPROACH - Luminița -Eugenia AVRAM; Elena VIZITIU (Editura Univeristatii "Stefan cel Mare" din Suceava, 2020)
In today's society, students' addiction to computers and mobile phones has grown. In this sense, the various researches show a major importance in training students of a system of knowledge and motivations, which will contribute to the formation of skills for the systematic practice of physical exercise throughout life. These motivations must be induced by the physical education teacher as well as by the parents. In order to obtain information on the importance and motivation of students to participate in physical education and sports in today's society, we used the questionnaire survey method. The questionnaire was applied to the students from the "Teodor V. Ștefanelli" Gymnasium School in Câmpulung Moldovenesc in order to obtain information about how and how much time they give to physical education and sports classes at the current stage. The respondents were 100 students from the gymnasium cycle, respectively grades V-VIII, students who have a computer and a mobile phone. Following the investigation, we came to the conclusion that it is necessary to permanently modernize the activity of physical education and sports in school in which it is necessary to find new methods, procedures and means to act in practice, as well as continuous improvement of existing ones for to easily attract students to this discipline.